Strategic Alignment Impacts on Organizational Performance in Indonesian Banking IndustrY - Iman, Nofie; Hartono, Jogiyanto (Gadjah Mada International Journal of Business, 2007)
Strategic alignment has attracted the attention of researchers and practitioners for the last 15 years. This paper reports findings from a survey on the impacts of strategic alignment on organizational performance in the Indonesian banking industry. The survey was conducted through internet-based and postal questionnaires sent to selected companies.Structural Equation Modeling (SEM) is utilized to apprehend the strategic alignment concept as an emergent variable derived from the co-variation ofÂ  level of business strategy and level of IS/IT strategy. Hence, we explore the role of this emergent concept as a determinant of organizational performance. Analysis of the data reveals a generally positive impact towards the organizational performance.